2004
DOI: 10.1002/jcp.20184
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium and/or theca are required for ATP‐elicited K+ current in follicle‐enclosed Xenopus oocytes

Abstract: The Xenopus follicular cell membrane is endowed with ATP-sensitive K+ channels, which are operated by various transmitters. These generate the ionic response named IK,cAMP via a mechanism that involves intracellular cAMP synthesis. It is known that opening these K+ channels favors oocyte maturation. Follicle stimulation by adenosine (Ado) or ATP consistently generates a strong IK,cAMP via activation of P1 and P3 purinergic receptors; however, ATP can also inhibit IK,cAMP, apparently acting on a third receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…P1 receptors on follicular cells mediate K + current responses, while P2Y 2 receptors are involved in the activation of Cl − currents [356]. These authors and others [329] suggested that these effects are consistent with intrafollicular ATP signalling that modulates oocyte maturation.…”
Section: Female Reproductive Organsmentioning
confidence: 81%
“…P1 receptors on follicular cells mediate K + current responses, while P2Y 2 receptors are involved in the activation of Cl − currents [356]. These authors and others [329] suggested that these effects are consistent with intrafollicular ATP signalling that modulates oocyte maturation.…”
Section: Female Reproductive Organsmentioning
confidence: 81%
“…Inhibition of I K,cAMP by purinergic agents is up-regulated in e.t.r. preparations, as shown previously (13). This effect was further studied by comparing the potency of UTP in w.f.…”
Section: Relationship Of Current Responses Elicited By Purinergic Agomentioning
confidence: 84%
“…For example, responses to ␤,␥-methylene-ATP (␤,␥-meATP), a P3 receptor agonist (10,11), were down-regulated in a significant fraction of e.t.r. follicles (13); however, these lower responses were inconsistent, apparently due to the well-known amplitude variability of current responses elicited by most agonists described in the Xenopus follicle. To reduce this variability, here, we compared the characteristics of the responses elicited by Ado and ATP, both in whole follicles (w.f.)…”
mentioning
confidence: 99%
See 2 more Smart Citations